الحس المأساوي في رواية بريد الليل لهدى بركات - إيمان قلول (My University, 2025)
Abstract: The novel "Burd of the Night" by Huda Barakat attempts to convey to the reader the phenomenon of tragedy in reality - expressing it as an attack and problem that affects society, shaping it in a creative literary form. Through the lens of fictional and humanitarian discourse, it reveals the reality of the Arab world and its pain. The study aimed to examine this in the first chapter titled *"The Tragic Sense and its Conceptual and Terminological Frameworks,"* focusing on the phenomenon of tragedy and its roles and mechanisms in portraying reality and reflecting it in some Arabic texts. In the analytical part titled *"The Tragic Sense in Huda Barakat's *Burd of the Night*,"* we analyzed the manifestations of tragedy reflected in the characters of the novel and the messages they convey, applying semiotic analysis methods. The effectiveness of the reading lies in how this comparative approach uncovers various aspects of the tragic reality, its representations, causes, forms, and how it is structured and reflected on the narrative discourse level. The novel, starting from its narrative title, to its characters, and reaching its places and earthly spaces, revolves around ----------------- الملخص: حاولت الروائية "هدى بركات" في روايتها بريد الليل أن تنقل للقارئ ظاهرة المأساة من الواقع - في تعبيرها عن هموم ومشكلات فئات في المجتمع إلى تشكيل فني ابداعي كشفت من خلاله العديد من القضايا الإنسانية ومرارة الواقع حاولت العربي واوجاعه. وقد تطلبت الدراسة الوقوف في فصلها الأول الذي بعنوان - الحس المأساوي: المفهوم والتجليات، على الحدود المفاهيمية لظاهرة المأساة، وجذورها عند العرب والغرب، وتجلياتها في بعض النصوص الأدبية. وفي الفصل التطبيقي الذي بعنوان - تجليات الحس المأساوي في رواية بريد الليل لهدى بركات وقفنا عند تجليات ظاهرة المأساة، التي عاشتها شخصيات الرواية من خلال رسائلهم، بتطبيق المقاربة السيميائية. ولعل فعالية القراءة في ضوء هذه المقاربة تكشف إلى حد كبير عن مختلف أزمات الواقع وتداعياته وأسبابه وأشكاله، وكيفية تشكيله وتمثله على مستوى الخطاب السردي للرواية، انطلاقا من دراسة عنوان الرواية، إلى شخصياتها، وصولا إلى الأمكنة والأزمنة. ---------------------- Resume: Dans son roman_ Corriere de nuit_ la romancière Hooda Barakat a tenté de transmettre au lecteur le phénomène tragique, depuis la réalité - dans son expression des préoccupations et des problèmes de groupes sociaux – jusqu’à a une création artistique créative, révélant de nombreuses problématiques humaines ainsi que l’amertume et la douleur de la réalité arabe. L’étude s’est concentrée, dans son premier chapitre, intitule- le sens tragique de concept et ses manifestation-, sur les limitions conceptuelles du phénomène tragique, ses racines chez les arabes et en occident, et ses analyses dans cet iris textes littéraires. Dans le chapitre applique intitule¨ Manifestations de sens tragique dans le roman¨-courrier de nuit- de Hooda Barakat, nous avons examine les manifestations du phénomène tragique vécues par les personnages du roman a travers leurs lettres, en appliquant une approche sémiotique efficacité de la lecture a la lumière de cette approche révèle peut-être dans une large mesure les différentes crises de la réalité, leurs répercussions ; leurs causes et leurs formes ; ainsi que la manière dort elles sont façonnées et représentées au narratif du roman, depuis l’étude du titre jusqu’à a ses jusqu’à passant par les lieux et les époques
Keywords: tragedy; the formation of reality; and alienation; المأساة، التشكيل، الواقع، الاغتراب; tragédie; formation; réalité; aliénation